Instagram as a social media tool about orthognathic surgery - S Kutalmış Buyuk; Tugce Imamoglu (Tabriz University of Medical Sciences, 2019)
Background: The aim of this short communication was to evaluate the quality and content of the Instagram posts about orthognathic surgery. Methods: Two hashtags #jawsurgery and #orthognathicsurgery were searched on Instagramin this retrospective Instagram post analysis study. Selected 100 posts for each hashtag were analyzed for type, total number of likes, comments, purpose and source. Results: Most of the posts about #jawsurgery were uploaded by patients (56.1%) who shared their personal experience. Most of the posts about #orthognathicsurgery also were uploaded by clinics (49.1%). Most of posts (39.6%) provided information about orthognathic surgery in #orthognaticsurgery. Posts generally involved by patient's experience (49.1%), followed by patient information (28.1%), and advertisement (22.8%) in #jawsurgery. Conclusion: Patients should be educated by orthodontists and maxillofacial surgeons about Instagram platform that it is not an adequate or accurate source of information about orthognathic surgery in its current form.